The Question of Metropolitan Form: Introduction - Anne Vernez Moudon; François Claessens; David Prosperi (Footprint)
Posing the concept of ‘metropolitan form’ as a question, as in the call for papers for this issue of Footprint, is an absolute necessity at this stage of development of urbanised areas. Many of the papers in this issue begin with the straw-man notion of a formless agglomeration of activities and spaces, the – for lack of a better phrase – postmodern urban experience.[1] There is a persistent theme in the related literatures of architecture, urban design and urban and regional planning that the physical form of the contemporary metropolis is un-describable. Soja’s six metaphors (post-Fordist industrial, cosmopolis, expolis, fractal city, carceral archipelago, simcities) are being indicative of the wide range of possible images.[2] The eight papers in this issue of Footprint take an opposite approach. They begin to trace the contours of the debate around how the noun ‘metropolitan form’ might be understood, how it might be studied, and how it might be possible to move from an empirical understanding of its structure to more intuitive design solutions.